Artificial Intelligence-Assisted Islamic Religious Education: Enhancing Students' Critical Thinking and Ethical Awareness in the Digital Era - Husna Husna; Khalid Abdullah Al Muzaini; Maryam Rashid Saleh Al Tamimi; Muneera Mohammed Al Dossary (PT Barkah Ilmi Fiddunya, 2024)
The rapid advancement of artificial intelligence (AI) has significantly transformed educational practices, including Islamic Religious Education (IRE). However, limited studies have comprehensively examined the integration of AI to simultaneously enhance students' critical thinking and ethical awareness within Islamic educational contexts. This study aims to analyze the effectiveness of AI-assisted learning in improving students' critical thinking skills while strengthening Islamic ethical values in secondary education. The research employed a mixed-method approach using a sequential explanatory design. Quantitative data were collected through pretest-posttest assessments involving 240 students from Islamic senior high schools, while qualitative data were obtained through classroom observations and in-depth interviews with teachers and students. The findings indicate that AI-assisted learning significantly improves students' analytical thinking, problem-solving ability, learning engagement, and digital literacy. Moreover, when integrated with Islamic ethical principles, AI encourages responsible technology use, strengthens moral reasoning, and promotes reflective learning behaviors. Teachers also demonstrated improved instructional innovation through adaptive learning strategies supported by AI applications. The novelty of this study lies in proposing an integrative framework that combines artificial intelligence, critical thinking development, and Islamic ethical education within a holistic instructional model, providing a new paradigm for digital transformation in Islamic Religious Education